2014
DOI: 10.1038/tp.2014.116
|View full text |Cite
|
Sign up to set email alerts
|

Identifying individual differences of fluoxetine response in juvenile rhesus monkeys by metabolite profiling

Abstract: Fluoxetine is the only psychopharmacological agent approved for depression by the US Food and Drug Administration for children and is commonly used therapeutically in a variety of neurodevelopmental disorders. Therapeutic response shows high individual variability, and severe side effects have been observed. In the current study we set out to identify biomarkers of response to fluoxetine as well as biomarkers that correlate with impulsivity, a measure of reward delay behavior and potential side effect of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 55 publications
5
23
0
Order By: Relevance
“…Impulsive behavior in macaques was previously shown to be a behavioral effect of fluoxetine treatment (He et al, 2014). For correlation with metabolomics data we carried out Beta regression to identify metabolites associated with impulsive behavior in the fluoxetine treated group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Impulsive behavior in macaques was previously shown to be a behavioral effect of fluoxetine treatment (He et al, 2014). For correlation with metabolomics data we carried out Beta regression to identify metabolites associated with impulsive behavior in the fluoxetine treated group.…”
Section: Resultsmentioning
confidence: 99%
“…The cohort of male rhesus monkeys ( Macaca mulatto ) that were sampled for this study has been described previously (He et al, 2014; Golub et al, 2015). At approximately 1 year of age animals were selected from the outdoor colony at the CNPRC, relocated to indoor caging, and assigned to treatment (fluoxetine) or control (vehicle) groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, fluoxetine can also directly inhibit MAOA activity (34). In metabolomics studies of juvenile rhesus we found that fluoxetine administration interacted with MAOA polymorphism genotype in influencing metabolites in plasma and cerebrospinal fluid (35) indicating a biological basis for an interaction between fluoxetine and MAOA.…”
Section: Introductionmentioning
confidence: 98%
“…The ages of the rhesus macaque subjects in the present study (one to four years of age) correspond roughly to four to twelve year-old children. Previous reports from this project have described dose selection (Golub and Hogrefe, 2014), metabolomic biomarkers of drug action (He et al, 2014), bone growth (Golub et al, 2015), sleep disturbance (Golub and Hogrefe, 2016), and social interaction (Golub et al, 2016). …”
Section: 0 Introductionmentioning
confidence: 99%